2017
DOI: 10.1103/physrevlett.119.054501
|View full text |Cite
|
Sign up to set email alerts
|

Mass and Moment of Inertia Govern the Transition in the Dynamics and Wakes of Freely Rising and Falling Cylinders

Abstract: In this Letter, we study the motion and wake-patterns of freely rising and falling cylinders in quiescent fluid. We show that the amplitude of oscillation and the overall system-dynamics are intricately linked to two parameters: the particle's mass-density relative to the fluid m * ≡ ρp/ρ f and its relative moment-of-inertia I * ≡ Ip/I f . This supersedes the current understanding that a critical mass density (m * ≈ 0.54) alone triggers the sudden onset of vigorous vibrations. Using over 144 combinations of m … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 39 publications
(64 reference statements)
5
45
7
Order By: Relevance
“…For the same Re d , the Strouhal number values they computed were thus lower for cylinders of fixed spanwise length. Finally, it can be pointed out that Namkoong et al (2008) observed numerically that for 66 < Re d < 185 the degrees of freedom in rotation and translation of an infinitely long (i.e. two-dimensional) cylinder lead to a slight decrease in the frequency of vortex shedding and of the associated oscillatory motion of the cylinder, with typically St BvK 0.17 for ρ = 1.01 and Re d = 156, corresponding to the trend observed here for lower Re d ( figure 19).…”
Section: Wake Visualization and Analysismentioning
confidence: 98%
See 2 more Smart Citations
“…For the same Re d , the Strouhal number values they computed were thus lower for cylinders of fixed spanwise length. Finally, it can be pointed out that Namkoong et al (2008) observed numerically that for 66 < Re d < 185 the degrees of freedom in rotation and translation of an infinitely long (i.e. two-dimensional) cylinder lead to a slight decrease in the frequency of vortex shedding and of the associated oscillatory motion of the cylinder, with typically St BvK 0.17 for ρ = 1.01 and Re d = 156, corresponding to the trend observed here for lower Re d ( figure 19).…”
Section: Wake Visualization and Analysismentioning
confidence: 98%
“…The problem of an infinitely long circular cylinder free to move in any direction perpendicular to its axis is a two-dimensional counterpart to the case of the sphere, and its characteristic dimension D is the cylinder diameter. To investigate the coupling between the wake instability and path oscillations, Namkoong, Yoo & Choi (2008) performed numerical simulations of the two-dimensional motion of a freely falling/rising infinitely long circular cylinder in an infinite fluid, but considered also situations of partially restrained motion in translation and rotation of the body. They focused on density ratios 0.5 < ρ < 4 and Reynolds numbers between 65 and 185, corresponding to an unsteady wake exhibiting periodic vortex shedding in the case of a fixed cylinder.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that added mass coefficients m * a for oscillating cylinders depend on a variety of parameters, including the frequency of oscillation, distance to boundaries, free surfaces, etc. Most studies have focused on the case of cylinders near a free surface and for small oscillations (Dong 1978;Konstantinidis 2013;Koo & Kim 2015;Tatsuno & Bearman 1990;Mathai et al 2017Mathai et al , 2018. However, in complex situations with relative motions, curved trajectories and unsteady three-dimensional wakes with flow separation, m * a can deviate significantly from the two-dimensional potential flow added mass coefficient.…”
Section: Model Equation Of Motionmentioning
confidence: 99%
“…Although the mean forces on the particle can still be approximated, the instantaneous drag and lift can no longer be described using simplified coefficients. Furthermore, owing to the lightness of the particle, this regime paves way for a strong coupling between the unsteady wake dynamics and the particle motion, often resulting in vigorous path instabilities (Brücker 1999;Ern et al 2012;Mathai et al 2016bMathai et al , 2017Mathai et al , 2018bMougin and Magnaudet 2006). As reported in Risso (2017), there is, today, compelling evidence that the wakes and dynamics of isolated buoyant particles are remarkably robust to turbulent perturbations (Ford and Loth 1998).…”
Section: Wake-driven Dynamics and Path-instabilitiesmentioning
confidence: 97%